2020
DOI: 10.1111/ajt.15773
|View full text |Cite
|
Sign up to set email alerts
|

Iron overload as a risk factor for hepatic ischemia-reperfusion injury in liver transplantation: Potential role of ferroptosis

Abstract: Hepatic ischemia-reperfusion (I/R) injury is a major problem in liver transplantation (LT). Although hepatocyte cell death is the initial event in hepatic I/R injury, the underlying mechanism remains unclear. In the present study, we retrospectively analyzed the clinical data of 202 pediatric living donor LT and found that a high serum ferritin level, a marker of iron overload, of the donor is an independent risk factor for liver damage after LT. Since ferroptosis has been recently discovered as an iron-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
149
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(154 citation statements)
references
References 39 publications
5
149
0
Order By: Relevance
“…5,17,18 Emerging evidence suggested that ferroptosis occurs in multiple organs under ischemia conditions, such as heart IR 19 or even liver transplantation in the clinical setting. 20 Moreover, ferroptosis have been implicated in intestinal IR-induced lung injury caused by the release of bacteria-derived endotoxins and pro-inflammatory cytokines from remote injured tissue. 21,22 Thus, an improved understanding of the mechanisms underlying ferroptosis after IR is critical for identifying potential therapies to prevent and mitigate LIRI-induced graft damage.…”
Section: Introductionmentioning
confidence: 99%
“…5,17,18 Emerging evidence suggested that ferroptosis occurs in multiple organs under ischemia conditions, such as heart IR 19 or even liver transplantation in the clinical setting. 20 Moreover, ferroptosis have been implicated in intestinal IR-induced lung injury caused by the release of bacteria-derived endotoxins and pro-inflammatory cytokines from remote injured tissue. 21,22 Thus, an improved understanding of the mechanisms underlying ferroptosis after IR is critical for identifying potential therapies to prevent and mitigate LIRI-induced graft damage.…”
Section: Introductionmentioning
confidence: 99%
“…In a murine model of hepatic I/R injury, lipid peroxidation and ferroptosis marker PTGS2 were elicited, all of which were markedly prevented by Fer-1 or αtocopherol. The mice fed with high iron diet represented deleterious I/R injury due to overload, and these manifestation was attenuated by DFO 104 . Furthermore, Li et al found that ferroptosis inhibition by Lip-1 significantly decreased myeloperoxidase (MPO) activity and mitigated histological injury in liver 100 .…”
Section: Other Liver Diseasesmentioning
confidence: 99%
“…Moreover, hepatic I/R injury induces inflammatory cascade and immunological reactions, which dampens normal graft liver function and leads to poor prognosis of the recipients 103 . Iron load of the donor has been proved to be an independent risk factor for hepatic I/R injury in pediatric living donor LTx 104 . In a murine model of hepatic I/R injury, lipid peroxidation and ferroptosis marker PTGS2 were elicited, all of which were markedly prevented by Fer-1 or αtocopherol.…”
Section: Other Liver Diseasesmentioning
confidence: 99%
“…Furthermore, investigation of IR injury in combination with a macrovesicular steatotic model also becomes essential, as studies have shown that such livers are more susceptible to IR injury compared with microvesicular steatosis. Interestingly, ferroptosis, an iron-dependent non-apoptotic cell death pathway, has been linked to hepatic IR injury [ 145 ]. A recent study in a murine model of hepatic IR injury has shown the upregulation of the ferroptosis marker prostaglandin-endoperoxide synthase 2 ( Ptgs2) after IR insult which was prevented by the ferroptosis inhibitor, ferrostatin-1 (Fer-1) or α-tocopherol [ 145 ].…”
Section: Necroptosis In Steatotic Hepatic Injury and Steatotic Irmentioning
confidence: 99%
“…Interestingly, ferroptosis, an iron-dependent non-apoptotic cell death pathway, has been linked to hepatic IR injury [ 145 ]. A recent study in a murine model of hepatic IR injury has shown the upregulation of the ferroptosis marker prostaglandin-endoperoxide synthase 2 ( Ptgs2) after IR insult which was prevented by the ferroptosis inhibitor, ferrostatin-1 (Fer-1) or α-tocopherol [ 145 ]. More studies are indeed required to investigate the involvement of ferroptosis during steatotic liver undergoing IR injury.…”
Section: Necroptosis In Steatotic Hepatic Injury and Steatotic Irmentioning
confidence: 99%